The Difference of Patient Satisfaction Between ISO and Non ISO Health Centers in Denpasar - A.A.A.A. Candrawati; I Ketut Suarjana; Dewa Nyoman Wirawan (Public Health and Preventive Medicine Archive, 2015)
Background and purpose: ISO has been implemented to improve quality of care and patient satisfaction in four health centers in Denpasar. An assessment of the quality of services has been conducted, but there has been no assessment of patient satisfaction. This study determined differences of patient satisfaction between ISO and non- ISO centers and related factors. Methods: The study design was cross-sectional sample survey of 298 respondents; 149 attending ISO clinics and 149 non-ISO clinics. Data were collected using self-administered questionnaires and analyzed with chi square test and logistic regression methods as well as quadrant analysis. Results: Satisfaction was significantly higher (p=0.001) among ISO health centers (98.66%) compared to non-ISO (87.25%). Satisfaction levels were significantly higher (p=0.001) among ISO health centers specifically for sub item reliability (97.99% vs 81.21%), responsiveness (97.32% vs 82.52%), assurance (98.66% vs 84.56%), empathy (97.32% vs 77.18%) and physical appearance (97.32% vs 83.8%). Multivariate analysis indicated that factors associated with patients satisfaction were ISO status (adjusted OR=16.56; 95%CI: 3.87-70.95) and health insurance membership (adjusted OR=3.76; 95%CI: 1.38-10.23). Quadrant analysis indicated that sub item politeness, carelessness and untidiness were priority area for improvement among ISO health centers. Conclusion: Patient satisfaction was significantly higher among ISO health centers. Study findings indicated that sub-items politeness, apparent carelessness and untidiness still to be improved among ISO health centers.